Características de virulência, resistência e diversidade genética de sorovares de Salmonella com impacto na saúde pública, isolados de frangos de corte no Brasil - Mendonça, Eliane Pereira (2016)
Salmonella Enteritidis, S. Typhimurium and S. Infantis are often associated with cases of human infections worldwide and is transmitted through consumption of contaminated food, particularly those of animal origin, especially chicken meat. This thesis was fractionated into three chapters, the first one relating to general considerations about the topics discussed in the following chapters. The second chapter aimed to evaluate virulence characteristics, antimicrobial resistance and the genetic similarity of 51 strains of S. Infantis isolated in samples of poultry origin from an industry located in the state of São Paulo, Brazil, during the 2009 to 2010 period. The third chapter aimed to analyze 111 strains of S. Enteritidis, 45 of Salmonella Typhimurium and 31 of Salmonella Typhimurium monophasic variant I 4, [5], 12:i:- isolated from chicken carcasses in different brazilian slaughterhouses from 2009 to 2011, and to estimate the risk to human health, based on the presence of virulence genes and antimicrobial resistance, correlating to the pathogenicity profiles (antimicrobial resistance and presence of virulence and resistance genes) with the genetic profile (ribogroup) of the isolates. To evaluate the antimicrobial susceptibility was performed the disk diffusion test for all serotypes of Salmonella, and exclusively to S. Enteritidis and S. Typhimurium, was also verified the minimum inhibitory concentration for ciprofloxacin and ceftazidime antibiotics. The presence of virulence genes invA (invasion), lpfA (fimbriae-adhesion), agfA (fimbriae-biofilm) and sefA (fimbriae-adhesion) were evaluated by PCR. The strains that showed resistance to antibiotics of β-lactams class were evaluated for the presence of resistance genes blaTEM, blaSHV, blaCTX-M and blaAmpC. For resistant strains to quinolones and fluoroquinolones antibiotics classes were searched the qnrA and qnrS genes. The phylogenetic relationship among the isolates was determined by RAPD method for S. Infantis strains, and by ribotyping technique to S. Enteritidis and S. Typhimurium.